Model Pemberdayaan Pertanian dan Kebijakan Pembangunan Dalam Mewujudkan Pilar Keamanan Pangan - Asnamawati, Lina; Herawati, Is Eka; Saleha, Eha; Yuliawati; Nurmalia, Ana (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2024)
Community empowerment is an economic development concept that outlines community values to create a new paradigm in development that is people-centered and participatory. The Systematic Literature Review (SLR) approach was used by the researchers to perform their investigation. To capture worldwide trends from previous research, data was analyzed using Microsoft Excel and the Bibliometric tool. The Prism Protocol was used to collect data. An in-depth examination of 44 papers on farmer empowerment and agricultural development policies to achieve sustainable food was undertaken. According to the study's findings, the four pillars of food security are availability, affordability, usage, and stability, and empowerment should play a part in strategic food and nutrition strategies from 2020 to 2024. Empowerment stresses the acquisition of sufficient skills, knowledge, and abilities.